PEMANFAATAN BIJI KARET DAN LIMBAH IKAN PATIN SEBAGAI BAHAN PEMBUATAN PAKAN IKAN, PUPUK ORGANIK CAIR DAN PAKAN UNGGAS - Hadinoto, Hadinoto; Suhesti, Eni; Suwarno, Eno (Fakultas Kehutanan Universitas Lancang Kuning, 2017)
Rubber trees planted by people in several districts of Riau province, among them the Kampar regency. Rubber seed that has not valuable feed source can be used for one of them is a main ingredient of fish feed. In addition to rubber seed, Tower Island Village also produces waste Patin fish entrails. The waste generated from the business community to make smoked fish Patin. During this time the waste is dumped in waterways around residences. Problems IbM partners: 1) Partners have the willingness to do busine ss, but do not have the knowledge and skills in the field of production, 2) Partners do not have knowledge in aspects of business management, which is a way of packaging, marketing, and business analysis calculations. Solutions are performed: training and assistance for people with the target communities to utilize the waste around them. Outputs from this IbM activities include: 1) The method of making rubber seed flour; 2) Method of making the feed / fish pellet made from rubber seed flour; 3) The method o f making a liquid organic fertilizer from waste fish entrails catfish; 4) Method of manufacture of poultry feed from catfish waste; 5) rubber seed flour; 6) Feed / fish pellet; 7) liquid organic fertilizer; 8) feed poultry. Mitra has begun to open wawasany a in utilizing waste rubber seed and catfish after receiving an explanation from the team. Partners receive initial skills in the utilization of fish waste and rubber seeds to manufacture pellets of fish, organic liquid fertilizer and poultry feed.